PENGARUH SISTEM INFORMASI ADMINISTRASI KEPENDUDUKAN TERHADAP KINERJA PELAYANAN DI KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PAREPARE - Alfathur, Ery (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2022)
This study aims to analyze and explain the effect of the population administration information system applied to the Department of Population and Civil Registration on the performance of services to the community. The population in this study was 57 employees and used a total sampling technique. The data collection techniques used were observation, documentation, and questionnaires. Meanwhile, the data analysis technique used was simple linear regression analysis. The results showed that the population administration information system had a significant effect on service performance at the Office of Population and Civil Registration of Parepare City. This is supported by the results of data processing which shows that the value of Sig = 0.000 < = 0.05 so that Ho is rejected and Ha is accepted so that it is stated that there is a significant influence between the population administration information system on the performance of employee services at the Office of Population and Civil Registration of Parepare City.